Tantangan Modern Dalam Menjaga Integritas Hakim: Mengatasi Ancaman Terhadap Keluhuran Martabat Profesional - Mawardi, Chalik; Akhdloriy, Abdurrahman Al Al (JATIJAJAR LAW REVIEW, 2024)
The integrity of judges is at the core of a fair and effective justice system, but is faced with complex challenges in this modern era. Two crucial aspects that need to be considered are the influence of information technology and the threat of corruption and political interference on the independence of judges. The information technology revolution makes it easier to access information but also brings new risks related to data security, privacy and information manipulation. Meanwhile, the threat of corruption and political interference can damage the integrity and independence of judges in making legal decisions. This paper highlights the importance of maintaining the integrity of judges as the main foundation in a fair and effective justice system. Through an in-depth understanding of the dynamics that influence public trust in the justice system, it is hoped that effective strategies can be developed to overcome these threats, strengthen judicial institutions, and maintain the integrity of the professional dignity of judges in the ever-developing modern era.